Consumo de drogas y alcohol. De la agenda pública a la agenda social de los gobiernos subnacionales. La experiencia de la Provincia de Santa Fe (Papeles, 2021)
The problematics associated to the consumption of drugs are part of the social agenda and actual policies of the states. However, this subject is presented in the agenda in a polysemic way, therefore the punitive health and social areas are tightly entwined. The consumption of substances is a global phenomenon that acquires its oun features in each territory. The cities stand as the first link of contact with the urban population, this is why the governments of urban areas are exposed to the necessity of providing real answers to this increasing problematic that is also lived very closely by the whole community. In carrying out this work we intend to 1st provide an accurate diagnosis of current debates on the approaches to the problematics of drugs and alcohol consumption. In 2nd place we´ll focus on recovering learning experiences from The Agency for the Prevention of Drug Use and integrated treatment to Addictions (APRECOD), belonging to the Ministery of Governments and Reform of the State of Santa Fe Province, during the years 2017 of 2019. Highlighting the mail role that subnational governments have in the building of social urban policies that should give answers to an integrated approach of this complex problematic.
Keywords: social policies; local government; prevention; consumption of substances; integrated approach